Al fitan : fitnah dan kehidupan akhir zaman / al-Hafizh Abu al-Fida' Ibnu Katsir ad-Dimasyqi ; penerjemah, Syamsuri ; penyunting, Halis Kurniawan, Artawijaya - AD-DIMASYQI, Abu al-Fida Ibnu Katsir , al-Hafizh; Syamsuri; Halis Kurniawan; Artawijaya (Hanif, 2011)
1109 hlm. ; 24 cm.